Correlation Between Body Mass Index and Cardiovascular Fitness in Medical Student - Alief Dhuha; Berry Rahmadhoni; Lovea Ajeng Sari; Dian Puspita; Resti Rahmadika Akbar; Widia Sari (Scientific Journal, 2025)
Introduction: Cardiovascular fitness is one of the components that can be used to evaluate health-related physical fitness. Body mass index (BMI) is a factor that can influence cardiovascular fitness. This is due to the strong correlation between BMI and cardiovascular fitness. Aims: To assess the correlation between BMI and cardiovascular fitness among medical students at Universitas Baiturrahmah. Method: The research was conducted at the Physiology Laboratory, Faculty of Medicine, Universitas Baiturrahmah. We assessed each subjects’s BMI and evaluated their cardiovascular fitness using the Harvard Step Test. The data were processed using Spearman rho correlation analysis. Results: Among the 50 subjects who participated in this study the mean BMI was 23.66±0.67 kg/m2, with approximately 68% (34) of subjects categorized in the normal BMI group. Out of the total number of subjects, around 34% (17) subjects had good cardiovascular fitness, with a mean value around 75.48±2.17. The results showed a significant correlation between BMI and cardiovascular fitness (r = -0.436, p<0.05), indicating that a higher BMI is related to lower levels of cardiovascular fitness. Conclusion: The results of this study indicate a significant negative correlation between BMI and cardiovascular fitness among medical students at Universitas Baiturrahmah.